مظاهر الوقف العلمي في الحضارة الإسلامية - فرحات, الكاملة (جامعة الوادي University of Eloued, 2017)
يتلخص مضمون بحثنا في الحديث عن الوقف في الشريعة الإسلامية، وبالتحديد على مظاهر الوقف العلمي في حضارتنا الإسلامية عبر تاريخها في مراحله المختلفة، فقد كان للوقف العلمي دور فعّالا في نشر العلم والثقافة، وتنوير العقل المسلم، بحيث ساعد في القضاء على ظاهرة الأمية في المجتمعات الإسلامية على مر العصور، كما أنه ساعد المعوزين في التحاقهم بالمدارس والكتاتيب، فأدى كل ذلك لازدهار الحركة العلمية والثقافية، وقد تمثلت مظاهر هذا الوقف العلمي في بناء المساجد والمدارس والكتاتيب ووقف الكتب والمكتبات وإنشاء الربط والخوانق والزوايا والخلاوي، وغيرها من الأماكن والأشياء التي تخدم طلبة العلم والمتعلمين في مختلف تخصصاتهم وأعمالهم، وتساعد في ذات الوقت الأساتذة والباحثين في بحوثهم وإبداعاتهم المختلفة ما أنتج لنا الآلاف من الكتب في الفنون المختلفة. The research's content is summed up to tackle the endowment in the Islamic law (Shari'a) and more precisely the endowment's aspect in our Islamic civilization throughout its different historic periods, Scientific endowment had a crucial role in spreading knowledge and culture and enlightening the Muslim psyche in the sense that it helped to eradicate illiteracy in Islamic societies throughout history as well as helping the less fortunate to join schools and madras which lead the flourishing of the scientific and cultural movement. The scientific endowment's aspects were seen in the erection of mosques, schools and koranic schools and the endowment of books and libraries and the establishment of ribat, khankahs, zawiyahs and khalwa and other places that help scholars in their specialties and works in one hand and teachers and researchers in their researches and creations in the other hand, Thus, we have thousands of books in a variety of arts.
Keywords: الوقف العلمي، الحضارة الإسلامية